2021
DOI: 10.1021/acs.jctc.0c01184
|View full text |Cite
|
Sign up to set email alerts
|

Force Field Optimization Guided by Small Molecule Crystal Lattice Data Enables Consistent Sub-Angstrom Protein–Ligand Docking

Abstract: Accurate and rapid calculation of protein-small molecule interaction free energies is critical for computational drug discovery. Because of the large chemical space spanned by drug-like molecules, classical force fields contain thousands of parameters describing atom-pair distance and torsional preferences; each parameter is typically optimized independently on simple representative molecules. Here, we describe a new approach in which small molecule force field parameters are jointly optimized guided by the ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(111 citation statements)
references
References 60 publications
0
111
0
Order By: Relevance
“…Although GALigandDock utilizes Rosetta’s latest betanov2016 energy function (Park et al, 2021), which accounts for torsional strain energies of the ligand, in addition to using fitted van der Waals distances, solvation potentials, and partial charges, it was difficult to make conclusions between drug conformation/binding modes and interface scores in our models. Comparative ligand interface scores and probability density plots for all 2000 docked dofetilide, terfenadine, and E4031 structures can be found in Figures 10 , 11 , and 12 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although GALigandDock utilizes Rosetta’s latest betanov2016 energy function (Park et al, 2021), which accounts for torsional strain energies of the ligand, in addition to using fitted van der Waals distances, solvation potentials, and partial charges, it was difficult to make conclusions between drug conformation/binding modes and interface scores in our models. Comparative ligand interface scores and probability density plots for all 2000 docked dofetilide, terfenadine, and E4031 structures can be found in Figures 10 , 11 , and 12 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we show that non-inactivating mutations S620T and S641T block the inward shift of F627 via differing mechanisms, preventing potential conformational changes of the SF during inactivation. Lastly, hERG channel structural models exhibiting elements associated with their respective mutations (including the WT channel model) were combined with drug models of dofetilide, terfenadine and E4031 and subjected to docking studies using the Rosetta GALigandDock protocol (Park et al, 2021). Results show that while all drugs bound to key residues Y652 and F656 across all models, corroborating existing experimental evidence, only the S641A inactivation-enhancing mutant provided alternative state-dependent binding opportunities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, engineering or design of an enzyme–substrate complex requires almost atomic-level accuracy, which may not be reached with the molecular docking methods mentioned previously. Recently, a novel approach called GALigandDock was reported that enabled small molecule docking with sub-angstrom accuracy in the Rosetta framework by force field optimization ( Park et al, 2021 ). GALigandDock outperformed the top current docking approaches in a cross-docking benchmark set providing new directions for automated enzyme–substrate complex modeling.…”
Section: Module 2: Building the Enzyme–substrate Complexmentioning
confidence: 99%
“…Step V: Selecting top-scoring inhibitors Finally, we re-refine and re-score the top-scoring compounds from the preceding step, by energy minimization using Rosetta [36,37] (Figure 1b, Step V). This step serves to ensure that the selected substituents on the shared hinge-binding core are indeed compatible with one another, both structurally and energetically.…”
Section: Computational Approachmentioning
confidence: 99%